2016
DOI: 10.1016/j.parkreldis.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Sensory Testing in adults with Tourette syndrome

Abstract: Our data show that the perceptual threshold detection of externally applied sensory stimuli is normal in adults with GTS. This indicates that other perceptual mechanisms, such as abnormal central sensorimotor processing and/or aberrant interoceptive awareness might underlie the clinically significant sensory abnormalities in GTS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 12 publications
1
28
1
1
Order By: Relevance
“…Most TS patients report that tics are often responses to uncomfortable internal sensations, like a tickle in the throat before a cough; some experts conclude that these premonitory sensations may be the primary phenomenon rather than the observed tics. 29 Premonitory sensations in TS are correlated with sensory hypersensitivity 30 and interoceptive awareness, 31 yet peripheral sensation is normal, 32,33 so any sensory abnormality must be central. Since the OFC receives input from most sensory systems and projects to regions involved in visceral function, 34 abnormal white matter connections with OFC fit well with a sensory model of TS.…”
Section: Discussionmentioning
confidence: 99%
“…Most TS patients report that tics are often responses to uncomfortable internal sensations, like a tickle in the throat before a cough; some experts conclude that these premonitory sensations may be the primary phenomenon rather than the observed tics. 29 Premonitory sensations in TS are correlated with sensory hypersensitivity 30 and interoceptive awareness, 31 yet peripheral sensation is normal, 32,33 so any sensory abnormality must be central. Since the OFC receives input from most sensory systems and projects to regions involved in visceral function, 34 abnormal white matter connections with OFC fit well with a sensory model of TS.…”
Section: Discussionmentioning
confidence: 99%
“…The role of abnormal central sensorimotor processing has also been suggested by the findings of a recent study, in which the Quantitative Sensory Testing (QST) battery was used in 14 adult patients with TS and 14 controls (Schunke et al, 2016). The authors reported no significant difference in the threshold for detection of externally applied sensory stimuli between patients with TS and controls.…”
Section: Multimodal Hypersensitivitymentioning
confidence: 95%
“…This is relevant to patients with tics, as a clinical study showed that 80% of patients with TS reported heightened sensitivity to external stimuli, with examples among all five sensory modalities {74}. Of note, patients with TS do not demonstrate primary sensory deficits, suggesting that abnormal central sensorimotor processing and/or aberrant interoceptive awareness might underlie their clinically significant sensory abnormalities {75}. The USP-SPS has been shown to be psychometrically sound, with high sensitivity and acceptable specificity, suggesting its utility in assessing different sensory phenomena in patients of all ages.…”
Section: Measurement Of the Premonitory Urgementioning
confidence: 99%